Control de inventario aplicando la NIC 2 de la Empresa Royma S.A.S del cantón Ventanas durante el período 2022-2023. - Valverde Figueroa, Emely Dayana (2024)
Inventory control is a key process in companies since it allows optimal registration, storage and counting of products. Efficient control is essential for the use of the company's resources, adequate flow of merchandise, having an updated inventory which is essential to avoid inconveniences with customers, avoid losses due to theft or deterioration, in other aspects. The objective of the investigation is to determine the inventory management in the company Royma S. A of the Ventanas canton during the periods 2022-2023, through the application of investigative techniques. The present case study was carried out with a mixed approach, while its scope is descriptive. The types of research used are two: documentary and field. The investigative techniques applied are: interview and observation of the financial statements, where the values were obtained to calculate the financial ratios of inventory turnover in the two periods considered in this academic work. The results of the research allowed us to conclude that: Inventory control according to IAS 2 is a key process in companies since it allows optimal registration, storage and counting of products. Efficient control is essential for the use of resources, adequate flow of merchandise, having updated stocks, which is essential to avoid inconveniences with customers, avoid losses due to theft or deterioration, reduce storage costs and other events.